2018
DOI: 10.1002/slct.201802526
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Electrospun Nickel (II) Oxide Nanofibers and Its Application for Hydrogen Peroxide Sensing

Abstract: The aim of the present study is to report an alternative technique of creating nickel oxide (NiO) nanofibers, manufactured by facile and economical electrospinning process. The crystallinity nature of NiO nanofibers is investigated by X‐ray diffraction (XRD). Nanofibers morphology is examined by Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The diameter of the nanofibers is varying from of 100–150 nm. Furthermore, Selected Area Electron Diffraction (SAED) pattern revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Along with the development and application of nanomaterials, the researcher [8][9][10] has prepared Co3O4/GR composites with different morphologies and properties using various methods. Among them, Electrospinning technology has become a worldwide research hotspot, as shown in Figure 1, and various metal oxide fibers have been prepared [11][12][13][14]. The electrode material synthesized from Co3O4/GR nanofiber can improve the electrochemical properties of electrode materials, and have essential research significance.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development and application of nanomaterials, the researcher [8][9][10] has prepared Co3O4/GR composites with different morphologies and properties using various methods. Among them, Electrospinning technology has become a worldwide research hotspot, as shown in Figure 1, and various metal oxide fibers have been prepared [11][12][13][14]. The electrode material synthesized from Co3O4/GR nanofiber can improve the electrochemical properties of electrode materials, and have essential research significance.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to glucose detection, NiOOH/Ni­(OH) 2 redox couple is demonstrated for H 2 O 2 sensing when Ni-based nanomaterials are used as nonenzymatic active materials. There are numerous examples of Ni-based nonenzymatic glucose and H 2 O 2 sensors constructed by modifying the substrate with nickel nanoparticles, nickel–carbon hybrids, Ni–CNT composite, Ni–graphene composites, Ni­(OH) 2 /C nanoparticles, LaNiO 3 nanooxide, etc. , It has also been demonstrated that the sensor characteristics may simply be tuned via doping the electrochemically active thin films. For instance, Ding et al fabricated a novel amperometric nonenzymatic glucose sensor based on Au doped NiO nanobelts .…”
Section: Introductionmentioning
confidence: 99%